Secret writings of Hoshang Merchant - Merchant, Hoshang
Never a shrinking violet, Hoshang Merchant came out of the closet early in his youth. A bard, a teacher, and a lover who has lived many lives, he is the quintessential gay who once cross-dressed, and yet defies categorization. Here he recounts his extraordinary life and splendid experiences ranging across countries and cultures. His is a story of the prejudice and neglect that are part of everyday gay life, and how he channelled his despair into creating poetry. He quotes Rumi, Ghalib, and Mir, and writes with searing honesty about his long and short love affairs.